Linear Analysis for Stability Threshold for a Finite Flexibly Supported Journal Bearings Lubricated with Micropolar Fluids - Kumar, Mahesh (My University, 2010)
The aim of the present thesis is to investigate and predict theoretically the static and dynamic characteristics including the stability of hydrodynamic journal bearing lubricated with micropolar flied. The static characteristics examined for finite flexibly supported journal bearing are load carrying capacity and steady state attitude angle, and dynamic characteristics evaluated are non-dimensional stiffness and damping coefficients, critical mass parameter, whirl ratio and Geometric parameter considered for FDM analysis of flexibly supported finite journal bearing are lm, L/D, and mass ratio. The theoretical prediction of hydrodynamic pressure in the bearing is obtained by the solution of modified Reynolds equation satisfying the appropriate boundary conditions. The steady state pressure profile has been obtained by FDM. For dynamic pressure, using liberalized analysis, first order perturbation of eccentricity ratio and attitude angle are used, and the resulting equations are solved by finite difference method with successive over relaxation scheme.
M.E. (CAD/CAM and Robotics)
Keywords: Hydrodynamic Journal Bearing; Micropolar Fluids